SIKAP DONALD TRUMP DALAM UPAYA MENORMALISASIKAN HUBUNGAN ISRAEL DAN UNI EMIRATES ARAB PADA ABRAHAM ACCORDS 2020 - Oktaviani, Shufina; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The idiosyncratic character of Donald Trump significantly influenced his attitudes and policy choices during the process of normalizing relations between Israel and the United Arab Emirates. Prior to the agreement, relations between the two states were marked by political tension, as the UAE was part of the Arab League boycott of Israel. However, shared national interests and common threats encouraged the emergence of discreet diplomatic interactions. The Trump administration seized this opportunity by promoting normalization through the Abraham Accords as part of the United States’ broader Middle East foreign policy. Amid domestic pressure including public unrest related to the COVID-19 crisis and driven by Trump’s campaign promises to broker peace in the Middle East and strengthen Israel’s international standing, the Abraham Accords became a vehicle through which Trump sought to improve his political image and present himself as an architect of regional peace. The findings indicate that Trump’s behavior throughout the normalization process between Israel and the United Arab Emirates under the 2020 Abraham Accords reflects three key leadership traits. Ego-Ambition as he sought to restore his political image and secure a major Middle East agreement. Goal Oriented demonstrated by his selection of a team whose views aligned with his objectives, and Crusader Expansionist marked by his assertive and sometimes coercive approach in pushing Arab states to normalize relations with Israel. Keywords: United States Foreign Policy, AIPAC, Evangelical Christian Groups, Political Lobbying Groups, Israeli-Palestinian Conflict.